2008
DOI: 10.1073/pnas.0802159105
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect roles for Nodal signaling in two axis conversions during asymmetric morphogenesis of the zebrafish heart

Abstract: The Nodal signaling pathway plays a conserved role in determining left-sided identity in vertebrates with this early left-right (L/R) patterning influencing the asymmetric development and placement of visceral organs. We have studied the role of Nodal signaling in asymmetric cardiac morphogenesis in zebrafish and describe two distinct rotations occurring within the heart. The first is driven by an asymmetric migration of myocardial cells during cardiac jogging, resulting in the conversion of the L/R axis to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 19 publications
4
95
0
Order By: Relevance
“…3). It has been reported that spaw morphant displays disturbed cardiac bmp4 asymmetry as well as defective heart laterality (11,21), and reversed asymmetry of lefty2 is accompanied by reversed heart laterality (50). However, it is likely that if the left-sided Nodal is present, repression of the Nodal signal in the right LPM is less significant for cardiac bmp4 asymmetry and heart laterality (Figs.…”
Section: Discussionmentioning
confidence: 89%
“…3). It has been reported that spaw morphant displays disturbed cardiac bmp4 asymmetry as well as defective heart laterality (11,21), and reversed asymmetry of lefty2 is accompanied by reversed heart laterality (50). However, it is likely that if the left-sided Nodal is present, repression of the Nodal signal in the right LPM is less significant for cardiac bmp4 asymmetry and heart laterality (Figs.…”
Section: Discussionmentioning
confidence: 89%
“…During heart tube formation, the cardiac disc undergoes an asymmetric tissue rearrangement that includes rotation of the cardiac disc and local invagination at the right side. This reorganization results in the left side of the disc, ultimately forming the dorsal face of the heart tube [19][20][21] . It has been suggested that such rotational events may provide directed torsion in the heart tube, which in turn may drive directional looping 20,[22][23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…Mutant embryos with disrupted cilia-mediated fluid flow in the KV display a wide variety of laterality defects [17][18][19] . To determine whether the residual cardiac-specific directional bias in sfw mutants is the result of alternative signals under the control of KV function, we analysed heart-looping direction in dnaaf1 mutants with immotile cilia 18,19 . Surprisingly, dnaaf1 mutants or sfw/dnaaf1 double-mutant embryos still exhibited a significant preferred dextral heart loop ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nodal, a member of the transforming growth factor-b (TGF-b) family, has essential roles during embryogenesis, such as formation of mesoderm and patterning of left-right axis (Schier and Shen, 2000;Shen, 2007;Baker et al, 2008). Recently, we have shown that Nodal and its receptors, activin receptor-like kinase 7 (ALK7) and ALK4, are expressed in human ovarian cancer cells .…”
Section: Introductionmentioning
confidence: 99%